EFEKTIVITAS PROGRAM KELUARGA HARAPAN BAGI KELUARGA PENERIMA MANFAAT DI KELURAHAN DERI KECAMATAN SESEAN KABUPATEN TORAJA UTARA - Prof. Dr. Hasnawi Haris; Andi Aco Agus; Imanuel Imanuel (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2023)
Abstract: This study aims to determine 1) Profile of Family Hope Program (PKH) in Deri Village, 2) Implementation of Family Hope Program in Deri Village, 3) Determinants of Family Hope Program implementation in Deri Village. This research is qualitative research with descriptive analysis method. The data collection techniques used were observational interviews and documentation. The results showed 1) The family hope program in Deri Village is a program of the Ministry of Social Affairs of the Republic of Indonesia that provides conditional assistance to poor people who are registered in the integrated social welfare data and meet the criteria of health, education and social welfare components. The Family Hope Program provides assistance in the form of non-cash money whose nominal is adjusted to the criteria of each component and provides assistance to beneficiary families. 2) The family hope program in Deri sub-district has not been fully effective because in its implementation there are still several problems such as delays in disbursing funds, funds disbursed not as nominal as they should, the presence of beneficiaries whose assistance is not disbursed and lack of awareness of beneficiary families to attend monthly meetings in the mentoring range. 3) The determinants of the implementation of the family hope program in Deri sub-district are, Supporting factors: a) local government support, b) community access is quite easy, in this case information access and road access. Inhibiting factors: a) delay in disbursement of funds, b) aid funds are not disbursed and less than the nominal should be, c) there is still a lack of PKH companions, d) lack of awareness of PKH beneficiary families to attend regular meetings every month in the context of Family Development Session (FDS) assistance.